Taberna: a vision from the carnavalesc order - Delgado Solís, Diego (2018)
The following article discusses the structure of the collage in the poem La Taberna del Salvadoran Roque Dalton as a structure that enables carnival nonsense and linguistic sharp cutting and therefore a subversion of the established order on several levels: the body, the sexual, the divine. For analysis, the author uses key concepts of the theory of carnival by Mikhail Bakhtin.